2012
DOI: 10.1051/epjconf/20122501052
|View full text |Cite
|
Sign up to set email alerts
|

Some aspects of numerical simulation of control valves for steam turbines

Abstract: The contribution deals with the numerical simulation of air and steam flow through the model of control valve for steam turbines. Numerical simulations were compared with experimental measurements for the award of the same boundary conditions. Valve characteristics have been computed for individual travel heights and pressure ratios of two variants of seat inflow angle (90° and 60°). Some other aspects are discussed in the article-comparison of the axysymmetric and 3D modelling, influence of the computational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…If the force equals the force corresponding with the product of the annular area and the difference of pressures before and after the valve, the valve is unbalanced; if the force is lower, it is a balanced valve. The paper [2] describes results of calculations and measurements of flow-through characteristics of unbalanced valves with varying seat inflow angle and concepts corresponding to the further stated valves. In the following stage, research focused on phenomena in the balancing system and in particular the force characteristics of the plug of this balanced single-seat diffuser control valve.…”
Section: Epj Web Of Conferencesmentioning
confidence: 99%
“…If the force equals the force corresponding with the product of the annular area and the difference of pressures before and after the valve, the valve is unbalanced; if the force is lower, it is a balanced valve. The paper [2] describes results of calculations and measurements of flow-through characteristics of unbalanced valves with varying seat inflow angle and concepts corresponding to the further stated valves. In the following stage, research focused on phenomena in the balancing system and in particular the force characteristics of the plug of this balanced single-seat diffuser control valve.…”
Section: Epj Web Of Conferencesmentioning
confidence: 99%
“…The pressure ratio is a ratio between the static pressure on the outlet from the control valve and the total pressure on the valve inlet. It is determined by the formula (5). 5The proportional travel height is a real travel of the valve plug related to the critical diameter of the nozzle.…”
Section: (4)mentioning
confidence: 99%
“…The geometry was further adapted and simplified with this program. The main software tool for performing the numerical simulation of the flow was the ANSYS/FLUENT 13.0 program, the details of simulations are described in the thesis [5]. All the mathematical models were conceived without a balancing system.…”
Section: Numerical Simulations Of the Valvementioning
confidence: 99%
“…al. [9] studied a balanced steam turbine control valve with experiment and RNG k-e based simulation. The result showed that both geometry models determined similar flow characteristic curves in trend compared to the experimental results.…”
Section: Introductionmentioning
confidence: 99%